DIY Regional Government Policy Innovation to Upgrade Micro, Small, and Medium Enterprises in the Covid 19 Pandemic Era (Sibakul Jogja ) - Vicki Dwi Purnomo; Ariyanti Luhur Tri Setyarini (Jurnal Pengabdian Masyarakat Formosa, 2022)
The Covid 19 pandemic, which began to enter Indonesia since March 2020, has had a significant impact on the sustainability of Micro, Small and Medium Enterprises (MSMEs). The people's economy experienced a significant decline. MSMEs in the Special Region of Yogyakarta that rely on income from the tourism sector and shopping from nomads or immigrants, especially those who are studying, many then close their businesses due to the lack of transactions. The Government's policy that prohibits interaction to reduce the spread of Covid 19 forces the Regional Government to immediately make policy innovations to save the sustainability of MSMEs. This research identified a breakthrough by the Regional Government, in this case the DIY Cooperative and UKM Service in its efforts to save MSMEs, by launching the SiBakul Jogja Program (Information System for Development of Cooperatives and Business Actors in Jogja). What are the opportunities and obstacles in the future. The author conducted this research to provide input for improving SiBakul Jogja as a mainstay of UMKM in DIY. The author uses the interview method and the Secondary Data Analysis method, namely research from various types of documents such as books, papers, journals, news and so on.